2021
DOI: 10.1016/j.jbmt.2021.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy for the treatment of respiratory issues using Systemic Manual Therapy protocols

Abstract: Background The emergence of the Coronavirus (COVID-19) pandemic increased the need for an effective treatment for respiratory conditions exponentially. To meet this challenge, we reevaluated the effectiveness of our physical therapy protocols for respiratory conditions. Protocols of interest were categorized as decongestive, neurogenic, mechanical, and immune modulating. Objective The objective of this study is to evaluate which of our existing treatment protocols or pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The latter does not allow unifying manual influences taking into account the existing pathology of internal organs, especially cardiovascular. The effects of SMT on the respiratory system are associated with improved tidal volumes, and there are no insufficient data on cardiovascular effects [16][17][18][19]. A number of authors have shown changes in the autonomic regulation of cardiac rate according to HRV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter does not allow unifying manual influences taking into account the existing pathology of internal organs, especially cardiovascular. The effects of SMT on the respiratory system are associated with improved tidal volumes, and there are no insufficient data on cardiovascular effects [16][17][18][19]. A number of authors have shown changes in the autonomic regulation of cardiac rate according to HRV.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effect on the psycho-emotional state of patients was also observed [15]. Some studies have shown that SMT improves athletic performance, reduces spasticity of the athletes with cerebral palsy, increases forced vital lung capacity and forced exhalation, improves lung function and activity of the patients with chronic obstructive pulmonary disease, moreover it is even included into the respiratory treatment protocols [16][17][18][19]. Some attention was paid to the autonomic effects of SMT, which include the changes in heart rate variability (HRV), peripheral blood flow and skin conduction [20][21][22].…”
Section: Introductionmentioning
confidence: 91%
“…The positive effect on the psycho-emotional state of patients was also observed (Williams, N. et al, 2007). Some studies have shown that SMT improves athletic performance, reduces spasticity of the athletes with cerebral palsy, increases forced vital lung capacity and forced exhalation, improves lung function and exercise activity of the patients with chronic obstructive pulmonary disease, moreover it is even included into the treatment protocols (Cerqueira, M., 2019;Kachmar, O. et al, 2018;Halili, A., 2021;Simonelli, C. et al, 2019). Some attention was paid to the autonomic effects of SMT, which include the changes in heart rate variability (HRV), peripheral blood flow and skin conduction (Alsayani, K., et al 2021;Benjamin, J. et al, 2020;Amoroso Borges, B. et al, 2018).…”
Section: Introductionmentioning
confidence: 99%